Opportunity Integrate the Goat at Areal Plantation Base on The Pepper Crop - Ella, Andi; Kadang, M (Indonesian Bulletin of Animal and Veterinary Sciences, 2004)
Consume the domestic flesh mount, but is not made balance with the growth rate produce. One of its low factor is growth rate produce is limitation of forage because availibility offarm which is not adequate. Goat is represent the comodity of South Sulawesi, based on : (a) market opportunity, (b) beneficial price, with it is developing be increase as well namely 46.9%/year, (c) goats population have been developed 1 .33% but not yet fulfilled the market need, and (d) support and potency of natural resources. Beside that crop of pepper prospective developed in South Sulawesi, based on: (a) market opportunity due the increase ofdemand causes the average price increased by 103.96% (1995-1999) with the production increase 10.36% and productivity by 0.42 ton.ha/year, (b) resources potention: the area (8,258 ha) does not yet executed optimally, opportunity production increase 63 .86%, the uncultivated land that potential are 150,404 ha, (c) one of superior commodity with the development centre in Sinjai, Bulukumba, and Bantaeng regency (SIKUMBANG). Growth average ofthe area width (15.61%) is bigger than it is production (11 .8%) . Integrate the goat, pepper and gliricidia in farming system broadly 8,258 ha will yield 61, 935,000 kg of forages with the carrying capacities are 8.33 goats/ha. If there are 8 goats, they will be produce 1,460 kg/year of manure for compost product. Development of integrated goat in pepper plantation will be increase the productivity of livestock and crop of pepper and gliricidia. Compost affected to improve the crop productivity. Developing the system could reduce the production cost, and it turn, the farmers income will be increase. Key words: Integration, goat, gliricidia, pepper plantation